Treatment of patin pond water uzing ultrafiltration - Lily Fareeza, Razali (2014)
Patin fish or the scientific name Pangasius Sutchi is a freshwater fish river that is very popular especially in Temerloh, Pahang. It is known as a bright fish acted as a very high selling prices. The purpose of this study was to examine the water quality and the most important thing is to assess parameters that are present in the nitrogen cycle in aquatic systems. In a closed aquatic system, the cycle begins with the production of hydrogen or ammonia formation. Ammonia will be retained by the waste production of fish and fish food debris uncoupled. Ammonia is produced from aquatic systems can endanger the lives of fish in the slightest. Through the nitrogen cycle, ammonia is then converted to nitrite and finally nitrate. The parameters that must be met to ensure the nitrogen cycle that occurs in the water can be controlled. Parameters of pH, total dissolved solids, ammonia, nitrite and nitrate are the most important parameters considered in this study. Water samples will also be analyzed using Ultrafiltration (UF). UP aims to see its effectiveness in reducing the flux that occurs over the sample under pressure of 1-5 bar and the results show the decline of 20%-40% water quality parameters that occur on samples